A Simple Reliable Protocol for Cytogentically Stable Mass Propagation of Ornithogalum virens Lindl. (Plant Tissue Culture and Biotechnology, 2016)
Ornithogalum virens is a plant of horticultural importance but recently researches are focused on its medicinal importance. A simple reliable protocol has been standardized for micropropagation of O. virens to produce a cytologically stable progeny with least polysomatic variation of chromosome number. Among different explants, bulb scales showed the maximum potential for organogenesis. From a single bulb scale 37 bulblets have been produced within 16 weeks of inoculation. A low concentration of auxin with different concentrations of cytokinin is suitable for organogenesis. A higher level of auxin induces callus formation. Bulblet production was the maximum in the medium supplemented with 0.5 mg/l NAA and 2 mg/l 2iP. O. virens normally has a chromosome number of 2n=6. In nature it shows a common occurrence of polysomaty. The somatic plates that deviate from normal 2n=6 specially 2n=12 are of quite common occurrence (approximately 18?25% per root tip). Strikingly the tissue culture regenerants show a uniform chromosome number 2n=6, frequency of polyploidy being negligible. RAPD profile of the explants and its regenerants are almost same. Five primer sets give more number of bands with explants DNA. Moreover, the intensity of the bands of source plant is sometimes more than that of the regenerants. This may coincides with the fact that in the source plant the somatic chromosome number is 2n=6 and 12, whereas in regenerants it is 2n=6.Plant Tissue Cult. & Biotech. 26(1): 1-14, 2016 (June)